Speaking Style Modulates Morphosyntactic Expectations in Young and Older Adults: Evidence from a Sentence Repetition Task. Issue 9 (20th October 2020) - Engel, Alexandra; Hanulíková, Adriana
ABSTRACT: Previous research has shown that talker identity and speaking style affect the processing of morphosyntactic violations. The present study examined whether speaking style modulates comprehension and subsequent production of case variants in German prepositional phrases across the life span. To this end, we conducted a sentence repetition and completion experiment with young and older adults. After a familiarization phase with two talkers (one with a careful pronunciation and one with a casual pronunciation), participants were asked to repeat utterances produced by these two talkers. Critical case markers were replaced by white noise. The results showed a main effect of speaking style in the responses of both age groups, suggesting that young and older adults can adjust their expectations about variants usage to the talker's speaking style and can alter their subsequent production accordingly. These findings have implications for research on processing and producing morphosyntactic variation and expectation-based language processing.